Passiflora ketura, a New Species of Passiflora Section Decaloba (Passifloraceae) from Peru - Macdougal, John M.; Tillett, Stephen S. (Phytotaxa, 2022)
Passiflora ketura, a new species of Passiflora (Passifloraceae) endemic to the mountain forests in Amazonas Department, Northern Peru, is described and illustrated from herbarium material. It is compared to similar species and placed in subgenus Decaloba section Decaloba.